Ureterocystoneostomy in complex oncological cases with an “Uebelhoer” modified Boari bladder flap - Radtke, Jan Philipp; Korzeniewski, Nina; Huber, Johannes; Pahernik, Sascha; Hadaschik, Boris; Hohenfellner, Markus; Teber, Dogu (Langenbeck's archives of surgery, 2017)
PurposeThe study aims to describe the technique and analyze the outcome of an arcuated bladder incision with building of a triangular flap, first described by Uebelhoer (UBBF), as a modification of the classical rectangular Boari bladder flap (BBF), that is often viable, but can present difficulties, such as reduced flap vascularization and mobility in pretreated patients.MethodsTwelve consecutive patients with distal or mid ureteral leakage or stenosis, that underwent UBBF, were retrospectively analyzed. We assessed postoperative morbidity using Clavien-Dindo classification. Short- and long-term functional outcomes were assessed using glomerular filtration rate (GFR), ultrasound, and renal scintigraphy.ResultsPatients underwent UBBF during initial oncological surgery in five cases and due to ureteral defects following oncological surgery or radiotherapy in seven cases. Median patient age was 57 (interquartile range (IQR) 46-72), defect length was 7.5 cm (IQR 5-8 cm), and median follow-up period was 41 (IQR 36-48) months. In short-term follow-up, 11/13 postoperative morbidities were Clavien-Dindo level I-II complications, mostly infections. Two level IIIa complications occurred. One anastomotic leakage was treated sufficiently with temporarily ureteral stenting and one voiding disorder needed intervention. In the long-term follow-up, 84% of patients had improved or constant GFR. In the one-year renal scintigraphy, no urodynamically relevant voiding disorder occurred.ConclusionsThe UBBF is a reliable procedure to reconstruct ureteral trauma even in complex oncological, pretreated patients suffering from distal or mid ureteral defects.It can be performed easily by a modified arcuate incision and provides good long-term functional outcomes.